Typographic landscapes – reading the letters in the cities - Gouveia, Anna Paula Silva; Pereira, André Luiz Tavares; Farias, Priscila Lena; Barreiros, Gabriela Garcia (InfoDesign, 2007)
This paper presents and discusses some applications of fundamental concepts from epigraphy to the study of typography in urban landscape. Epigraphy is part of archaeology, more precisely of the field of palaeography. It studies inscriptions, ancient writing on enduring materials (such as stone, metal, clay, wax.), including deciphering, dating and interpretation of their messages. The paper proposes the application of epigraphic procedures to the study of modern inscriptions, figuring the names of architects and constructors found on the façades of buildings in São Paulo city historical centre. It demonstrates, therefore, how those concepts may be applied to the development of more precise methods of data gathering, systematization and cataloguing, that may be adopted in information design research.